Antioxidant and hepatoprotective role of selenium against silver nanoparticles - Ansar S (Dove Medical Press, 2017)
Sabah Ansar,1 Saad M Alshehri,2 Manal Abudawood,1 Sherifa S Hamed,3,4 Tansir Ahamad2 1Clinical Laboratory Sciences, Applied Medical Science, King Saud University, Riyadh, Saudi Arabia; 2Department of Chemistry, College of Science, King Saud University, Riyadh, Saudi Arabia; 3Zoology Department, College of Science, King Saud University, Riyadh, Saudi Arabia; 4Zoology Department, Faculty of Science, University of Alexandria, Moharram Bey, Alexandria, Egypt Abstract: Silver nanoparticles (AgNPs) have attracted the most interest in terms of their potential biomedical and industrial applications. However, these nanoparticles have shown their toxic behavior toward environment, living tissues, and organisms. Selenium (Se), an essential trace element, is necessary for various metabolic processes, including protection against oxidative stress and immune function. The present study was undertaken to evaluate the effect of Se against AgNP-induced hepatic oxidative stress. AgNPs were synthesized and then prepared nanoparticles were characterized using various analytical techniques such as UV-visible spectroscopy, X-ray diffraction, and transmission electron microscopy. Rats were administered AgNPs intraperitoneally (5 mg/kg/day) and Se (0.2 mg/kg) was given by gavage. AgNP administration induced hepatic damage as indicated by the serum marker enzymes with reduction in levels of glutathione, and decrease in activities of SOD, CAT, and GSH-peroxidase (P<0.05). Decrease in levels of total antioxidant capacity (TAC) and increase in level of C-reactive protein (CRP) was also observed in AgNP-treated group compared to control group. However, Se markedly attenuated AgNP-induced biochemical alterations, levels of TAC, CRP, and serum transaminases (AST, ALT) (P<0.05). Taken together, these findings suggest that administration of AgNPs produces hepatotoxicity in rats, whereas Se supplementation attenuates these effects. Keywords: silver nanoparticles, selenium, antioxidant enzymes, hepatotoxicity, oxidative stress